SOCIOCOGNITIVE CONFLICT AND DEVELOPMENT OF MENTALLY RETARDED CHILDREN. - Olivares Rodríguez, José; Rodríguez, Angel (Anales de Psicología / Annals of Psychology)
In the context of the investigations of the "Geneva School of Educational Social Psychology" on the influence of sociocognitive conflict upon the progress of normal children from a non-conservative to a conservative stage, we tested their hypothesis with a sample of mentally retarded children. In our experiment we established two experimental groups and a control group. Both experimental groups were exposed to conflicting social interaction (one with a correct-response model, and the other one with an erroneous-response model). The results indicate that both experimental groups differed significantly from the control group in the conservative-non conservative dimension the control group in the experimental treatment, and so did they still ten days thereafter. This allows us to consider the cognitive progress as consolidated, and to infer that the conflicting social interaction is an effective way of accelerating the mental progress not only of normal developed children -as often proved- but also of mentally retarded.